2010
DOI: 10.1098/rspb.2010.1923
|View full text |Cite
|
Sign up to set email alerts
|

Landscape-moderated biodiversity effects of agri-environmental management: a meta-analysis

Abstract: Agri-environmental management (AEM) is heralded as being key to biodiversity conservation on farmland, yet results of these schemes have been mixed, making their general utility questionable. We test with meta-analysis whether the benefits of AEM for species richness and abundance of plants and animals are determined by the surrounding landscape context. Across all studies (109 observations for species richness and 114 observations for abundance), AEM significantly increased species richness and their abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
433
7
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 520 publications
(474 citation statements)
references
References 63 publications
(102 reference statements)
26
433
7
8
Order By: Relevance
“…The greatest positive biodiversity response has been observed in landscapes with an intermediate level of 'complexity' -the degree of variation within landscape (Concepción et al 2012). Despite this, other studies have found inconsistent results for different taxonomic groups for both simple and complex landscapes, and that the effect of complexity depends on the type of surrounding vegetation (Batáry et al 2011). Landscapes with a greater proportion of area covered by management demonstrate stronger positive biodiversity response (Baker et al 2012;Dallimer et al 2010), although whether this is in response to direct agri-environment scheme investment or greater inclusion of suitable landscapes remains unclear.…”
Section: Landscape Scalementioning
confidence: 85%
See 4 more Smart Citations
“…The greatest positive biodiversity response has been observed in landscapes with an intermediate level of 'complexity' -the degree of variation within landscape (Concepción et al 2012). Despite this, other studies have found inconsistent results for different taxonomic groups for both simple and complex landscapes, and that the effect of complexity depends on the type of surrounding vegetation (Batáry et al 2011). Landscapes with a greater proportion of area covered by management demonstrate stronger positive biodiversity response (Baker et al 2012;Dallimer et al 2010), although whether this is in response to direct agri-environment scheme investment or greater inclusion of suitable landscapes remains unclear.…”
Section: Landscape Scalementioning
confidence: 85%
“…Recent studies have found that the biodiversity response to agri-environment scheme investment is influenced by the context of the surrounding landscape (Carvell et al 2011;Concepción et al 2012), although this response is inconsistent and poorly resolved (Batáry et al 2011). The greatest positive biodiversity response has been observed in landscapes with an intermediate level of 'complexity' -the degree of variation within landscape (Concepción et al 2012).…”
Section: Landscape Scalementioning
confidence: 99%
See 3 more Smart Citations